Analisis Kebutuhan Perangkat Pembelajaran E-Learning Berbasis Moodle pada Siswa SMP - Vica Windhi Seputri; Suparman Suparman (Jurnal Inovasi Pendidikan Matematika (JIPM), 2022)
Learning media using moodle-based e-learning is a dynamic web-based learning platform with an interactive online course management system and creates a personalized learning environment. Online learning activities carried out by teachers still use the same method when direct learning, especially in mathematics subjects that are classified as abstract. This study aims to analyze the needs of student learning tools during a pandemic like this time, which is being held for junior high school students. This research is a descriptive survey method. In this study, the data techniques used were non-test observation and interview techniques. The research data were analyzed descriptively. The instrument used in this study used interview sheets which were managed on some research samples and used literature studies, which were conducted on several junior high school students and mathematics teachers as samples. The results of this study indicate that the existence of online learning as it is today has resulted in a surge in internet users and is dominated by junior high school education. Teachers admit that they are not ready to carry out online learning, so most teachers teach only by providing materials and assignments to students. With this learning style, the concept of understanding students is still in doubt, so there is a need for learning media that can make a medium for students to learn online.